Pengaruh Kompensasi Dan Disiplin Kerja Terhadap Kinerja Karyawan Melalui Motivasi Kerja Sebagai Variabel Intervening Pada PT. Indah Cargo Logistik Jambi - Faiza Amanda Putri; Sumarni Sumarni; Dwi Kurniawan (Universitas 45 Surabaya, 2024)
The purpose of this research is to test and analyze the effect of compensation on employee performance, the effect of work discipline on employee performance, the effect of compensation on work motivation, the effect of work discipline on work motivation, the effect of work motivation on employee performance, and to test and analyze the effect of compensation on performance employees through work motivation, as well as testing and analyzing the influence of work discipline on employee performance through work motivation. This research uses a quantitative approach with explanatory research type. The sample in this study were employees of PT. Indah Cargo Logistik Jambi, totaling 54 using a saturated sampling technique. Data collection uses a questionnaire that has been tested for validity and reliability. The variables in this research are compensation (X1), work discipline (X2), work motivation (Z), and employee performance (Y). data were analyzed using SmartPLS 3.0 software. The research results show that compensation has a positive and significant influence on employee performance, work discipline has a positive and significant influence on employee performance, compensation has a positive and significant influence on work motivation, work discipline has a positive and significant influence on work motivation, work motivation has an influence positive and significant on employee performance, work motivation is able to provide a positive and significant influence in linking compensation to employee performance, and work motivation is able to provide a positive and significant influence in linking work discipline to employee performance.